The effect of outdoor education games with motivation level on student's physical fitness - Ally Selamet Murdiono; Yudha Munajat Saputra; Indra Safari (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
This study aims to determine whether outdoor education games have an effect on increasing students' fitness with motivation. The research method used is an experimental method with 2x2 factorial, this research was conducted at SDN 2 Jatimunggul, Terisi District, Indramayu Regency with the samples collected were students of class V and VI SDN 2 Jatimunggul. The data analysis used in this research is the two way ANOVA test and the Tukey test with the help of the SPSS application. The results of this study are outdoor education games have an effect on increasing students' physical fitness, there is an interaction between outdoor education games and the level of motivation on students' physical fitness, fortified outdoor education games are better used than moving bomb games to increase physical fitness in the high motivation group, while in In the low motivation group, there was no significant difference between the two outdoor education games on increasing students' physical fitness